Integral field spectroscopy with the Gemini Multiobject Spectrographs - Allington-Smith, J; Murray, G; Content, R; Dodsworth, G; Miller, B; Turner, J; Jorgensen, I; Hook, I (2002)
We describe the integral field unit (IFU) which converts the Gemini Multiobject Spectrograph (GMOS) installed on the Gemini-North telescope to an integral field spectrograph, which produces spectra over a contiguous field of view of 7×5 arcsec with spatial sampling of 0.2 arcsec over the wavelength range 0.4-1.0 μm. GMOS is converted to this mode by the remote insertion of the IFU into the beam in place of the masks used for the multiobject mode. A separate field of half the area of the main field, but otherwise identical, is also provided to improve background subtraction. The IFU contains 1500 lenslet-coupled fibres and was the first facility of any type for integral field spectroscopy employed on an 8/10 m telescope. We describe the design, construction and testing of the GMOS IFU and present measurements of the throughput both in the laboratory and at the telescope. We compare these with a theoretical prediction made before construction started. All are in good agreement with each other, with the on-telescope throughput exceeding 60% (averaged over wavelength). Finally we show an example of data obtained during commissioning to illustrate the power of the device.